(untitled) (Khairulummah, 2022)
The role of poetry, films, and videos in fueling sectarianism is one of the challenging issues. Poetry, often a medium for expressing deep feelings, emotions and beauty, reflects humanity’s aesthetic and artistic sensibilities. In Islam, while there’s no prohibition on poetry itself, there’s a distinction: negative and harmful poetry that provokes hatred and animosity or oppresses others is condemned in the Quran and Sunnah of the Prophet (pbuh). On the other hand, positive, ethical and moral poetry is admired and praised, as proven by the Prophet’s (pbuh) appreciation for virtuous poets. Unfortunately, modern times witness a prevalence of contentious and divisive poetry that promotes animosity and hatred among different societal groups, leading to a culture of hatred , and conflict. This tendency not only promotes violence but also results in unjust loss of many innocent lives, contradicting religious and golden ethical principles of Islam. This article is structured into four parts. The first explores various forms of poetry, the second delves into poetry’s status in pre-Islamic era, the third presents Islam’s standpoint on poetry, and the final section dissects sectarian-based poetry and its various characteristics. It concludes with suggestions to address this issue in a meaningful way.